SISTEM INFORMASI BERBASIS WEB UNTUK MONITORING BELAJAR MENGAJAR PADA SMA KRISTEN GAMALIEL - Eunike Stacy Winardy; Marlina; Hasniati (STMIK KHARISMA Makassar, 2017)
This research aims to help Gamaliel Christian high school curriculum part in monitoring the continuity of learning materials given by the teacher in teaching and learning in the classroom in compatible with the schedule is by using applications that support. Applications that use web-based so as to facilitate the curriculum and teachers in providing information to all parties involved.